Ecological Leadership of Kiai M. Faizi - HS, Dedi Eko Riyadi; Zuhri, Achmad Muhibbin; Salik, Mohamad (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
This study aims to describe ecological leadership as a form of leadership of Kiai M. Faizi, who is concerned about environmental cleanliness, which is implemented in managing a waste-free Islamic boarding school, especially plastic waste. This study was conducted at the Annuqayah Islamic Boarding School in the Sawajarin area, using a qualitative approach with a phenomenological type. Data collection used a structured interview method with the caretaker, in-depth observation of ecological plastic waste-free practices, and documentation. The analysis method used the Moustakas structured pattern: 1) description of phenomena, 2) horizonalization, 3) cluster of meaning, and 4) essence description. The study results showed that M. Faizi's leadership in forming the ecological piety of students used two steps, namely, revitalization of religious teachings and role models and changing the slogan